Strategi Pembuatan Buku Esai Fotografi tentang Kehidupan Masyarakat Bandungan - Kurniawan, Daniel; ., Margana; ., Martien (Nirmana, 2010)
Bandungan is a countryside which has ten villages. The beauty of the scenery and the fresh air from Bandungan make it a tourist spot especially for tourists from Semarang, Ungaran, Ambarawa and Solo. Through time, Bandungan starts to suffer from irresponsible development. This book is designed as introduction to know Bandungan further about its function for society and citizens from the city around Bandungan. Hopefully through this book many people will recognize Bandungan not only as a spot for holidays and having fun but also realize its role in their lives, and that it will help reduce the exploitation of Bandungan and preserve its beauty. In this book, every potential from each village in Bandungan will be revealed through text which is combined with photography so the information will be easily understood and become more interesting.